Millennial Experience Traveling to Ecotourism - I Dewa Gde Satrya; Thomas S Kaihatu; Lexi Pranata Budidharmanto (Ilomata International Journal of Social Science, 2023)
Ecotourism has become an attraction that is increasingly in demand after the Covid-19 pandemic. The current millennial generation has various options for channelling their desire to travel. Ecotourism is one option. It is realized that this non-mainstream tourism genre is much liked by today's young generation who tend to want to go on an adventure looking for new experiences. Millennials are the generation born in 1980-2000, have the power to change trends and lifestyles, are connected to the internet, are all digital, and have a very high appeal to nature. Travel based on flora and fauna conservation, protecting endangered cultures, and education to support the sustainability of the universe, is the choice among millennials. The Turtle Conserva-tion and Education Center (TCEC) has a strategic role as the preferred ecotourism destination for millennial tourists. The research question are (1) what values grow from the experience of traveling to ecotourism desti-nations? (2) how is the internalization of deep memories through the experience of traveling to ecotourism destinations? The purpose of this study was to determine the value that grows from the experience of travel-ing to ecotourism destinations. This study used qualitative method, data collected through observations and interviews. The result of this study is that traveling to TCEC raises awareness of the environment among mil-lennials that nature must be treated with full respect, as well as showing respect for residents encountered on trips and enjoying interactions with residents while on tour. A deep impression of tourists is obtained through the experience of interacting with natural elements.